Habitat use differences mediate population threat exposure in white sturgeon - Jonathan A. Walter; Gabriel P. Singer; Daniel C. Reuman; Scott F. Colborne; Lawrence W. Sheppard; Daniel R. O’Donnell; Nat Coombs; Erin E. Tracy; Myfanwy Johnston; Emily A. Miller; Anna E. Steel; John T. Kelly; et al. (Environmental Biology of Fishes, 2026)

Analysis of host and gut microbial biotransformation products of kratom (Mitragyna speciosa) by mass spectrometry - William J. Crandall; Ken H. Liu; Choon M. Lee; Grant Singer; Jaclyn Weinberg; Edward T. Morgan; Dean P. Jones; Cassandra L. Quave (Phytochemistry Letters, 2025)

The East Palestine train derailment: A complex environmental disaster - Lynn T. Singer; Fredrick Schumacher; James Fabisiak; Laura J. Dietz; Timothy Ciesielski (Neurotoxicology and Teratology, 2025)

The relationships of prenatal cocaine exposure, postnatal lead exposure, and victimization to aggressive behavior/delinquency in adolescence - Khoa Duc Le; Jeffrey Albert; June-Yung Kim; Sonia Minnes; Meeyoung O. Min; Lynn T. Singer (Neurotoxicology and Teratology, 2025)

Co-occurring substance use and mental health symptoms among prenatally substance-exposed emerging adults - June-Yung Kim; Sonia Minnes; Meeyoung O. Min; Liat R. Johnson; Lynn T. Singer (Neurotoxicology and Teratology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Performance of anhydrous ethanol and gasoline blends on a SI engine: Decoupling evaporation enthalpy and knock resistance - M.E.S. Martins; T.D.M. Lanzanova; V.R. Roso; J.L.S. Fagundez; J.P. Silveira; R.T.G. Guilherme; F.F. Rovai; T. Kersten; T. Garbe; A. Singer; M. Jakob (Journal of Cleaner Production, 2024)

Melt inclusions in zircon: a window to understanding the structure and evolution of the magmatic system beneath the Laguna del Maule volcanic field - Kei Shimizu; Tyler B. Blum; Chloe E. Bonamici; John H. Fournelle; Christine E. Jilly-Rehak; Noriko T. Kita; Kouki Kitajima; Jacob D. Klug; Will O. Nachlas; Brad S. Singer; Michael J. Spicuzza; Alexander V. Sobolev; et al. (Contributions to Mineralogy and Petrology, 2024)

A river runs through it: Robust automated mapping of riparian woodlands and land surface phenology across dryland regions - Conor A. McMahon; Dar A. Roberts; John C. Stella; Anna T. Trugman; Michael B. Singer; Kelly K. Caylor (Remote Sensing of Environment, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Alkaloid content in microsporidia-infected Adalia bipunctata (Coleoptera: Coccinellidae) life stages, and pathogen spore load in adults after exposure to physical stress - T. Steele; R.D. Singer; S. Bjørnson (Journal of Invertebrate Pathology, 2023)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

Cognitive and functional outcomes at age 21 after prenatal cocaine/polydrug exposure and foster/adoptive care - Lynn T. Singer; Gregory Powers; June-Yung Kim; Sonia Minnes; Meeyoung O. Min (Neurotoxicology and Teratology, 2023)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Storage of orchid pollinia with varying lipid thermal fingerprints - Ceci Castilho Custodio; Nelson B. Machado-Neto; Rodrigo B. Singer; Hugh W. Pritchard; Philip T. Seaton; Timothy R. Marks (Protoplasma, 2020)

Low river survival of juvenile steelhead in the Sacramento River watershed - Philip Thomas Sandstrom; Arnold J. Ammann; Cyril Michel; Gabriel Singer; Eric D. Chapman; Robert Bruce MacFarlane; Steven T. Lindley; Abbott Peter Klimley (Environmental Biology of Fishes, 2020)

Estimation of metapopulation colonization rates from disturbance history and occurrence‐pattern data - H. Fabritius; A. Singer; J. Pennanen; T. Snäll (Ecology, 2019)
Occurrence patterns of many sessile species in dynamic landscapes are not in equilibrium due to their slow rates of metapopulation colonization and extinction. Colonization–extinction data enable the estimation of colonization rates for such species, but collecting the necessary data may require long waiting times between sampling years. Methods for estimating colonization rates of nonequilibrium metapopulations from single occurrence‐pattern data have so far relied on additional data on patch ages and on past patch connectivities. We present an approach where metapopulation colonization rates are estimated from occurrence‐pattern data and from disturbance history data that inform of past patch dynamics and that can be collected together with occurrence‐pattern data. We estimated parameter values regulating patch and metapopulation dynamics by simulating patch network and metapopulation histories that result in present‐like patch network configurations and metapopulation occurrence patterns. We tested our approach using occurrence‐pattern data of the epiphytic lichen Lobaria pulmonaria in Fennoscandian forests, and fire‐scar data that inform of the 400‐yr history of fires and host tree dynamics in the same landscapes. The estimated model parameters were similar to estimates obtained using colonization–extinction data. The projected L. pulmonaria occupancy into the future also agreed with the respective projections that were made using the model estimated from colonization–extinction data. Our approach accelerates the estimation of metapopulation colonization rates for sessile species that are not in metapopulation equilibrium with the current landscape structure.

Artificial light at night decreases biomass and alters community composition of benthic primary producers in a sub‐alpine stream - Maja Grubisic; Gabriel Singer; M. Cristina Bruno; Roy H. A. van Grunsven; Alessandro Manfrin; Michael T. Monaghan; Franz Hölker (Limnology and Oceanography, 2017)
Artificial light at night (ALAN) is recognized as a contributor to environmental change and a biodiversity threat on a global scale. Despite its widespread use and numerous potential ecological effects, few studies have investigated the impacts on aquatic ecosystems and primary producers. Light is a source of energy and information for benthic autotrophs that form the basis of food webs in clear, shallow waters. Artificial night‐time illumination may thus affect biomass and community composition of primary producers. We experimentally mimicked the light conditions of a light‐polluted area (approximately 20 lux, white LED) in streamside flumes on a sub‐alpine stream. We compared the biomass and community composition of periphyton grown under ALAN with periphyton grown under a natural light regime in two seasons using communities in early (up to 3 weeks) and later (4–6 weeks) developmental stages. In early periphyton, ALAN decreased the biomass of autotrophs in both spring (57% at 3 weeks) and autumn (43% at 2 weeks), decreased the proportion of cyanobacteria in spring (54%), and altered the proportion of diatoms in autumn (11% decrease at 2 weeks and 5% increase at 3 weeks). No effects of ALAN were observed for later periphyton. Further work is needed to test whether streams with frequent physical disturbances that reset the successional development of periphyton are more affected by ALAN than streams with more stable conditions. As periphyton is a fundamental component of stream ecosystems, the impact of ALAN might propagate to higher trophic levels and/or affect critical ecosystem functions.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Predictors of CNS injury as measured by proton magnetic resonance spectroscopy in the setting of chronic HIV infection and CART - J. Harezlak; R. Cohen; A. Gongvatana; M. Taylor; S. Buchthal; G. Schifitto; J. Zhong; E. S. Daar; J. R. Alger; M. Brown; E. J. Singer; T. B. Campbell; et al. (Journal of NeuroVirology, 2014)

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Progressive cerebral injury in the setting of chronic HIV infection and antiretroviral therapy - Assawin Gongvatana; Jaroslaw Harezlak; Steven Buchthal; Eric Daar; Giovanni Schifitto; Thomas Campbell; Michael Taylor; Elyse Singer; Jeffrey Algers; Jianhui Zhong; Mark Brown; Deborah McMahon; et al. (Journal of NeuroVirology, 2013)

Beyond climate change attribution in conservation and ecological research - Camille Parmesan; Michael T. Burrows; Carlos M. Duarte; Elvira S. Poloczanska; Anthony J. Richardson; David S. Schoeman; Michael C. Singer (Ecology Letters, 2013)
There is increasing pressure from policymakers for ecologists to generate more detailed ‘attribution’ analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change ( ACC ), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ‘ very high confidence’ [ sensu Intergovernmental Panel on Climate Change ( IPCC )] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.

Survival and movement patterns of central California coast native steelhead trout (Oncorhynchus mykiss) in the Napa River - P. T. Sandstrom; T. Keegan; G. Singer (Environmental Biology of Fishes, 2013)

Growth, survival, and tag retention of steelhead trout (Oncorhynchus mykiss) and its application to survival estimates - P. T. Sandstrom; A. J. Ammann; C. Michel; G. Singer; E. D. Chapman; S. Lindley; R. B. MacFarlane; A. P. Klimley (Environmental Biology of Fishes, 2013)

The effects of environmental factors on the migratory movement patterns of Sacramento River yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) - Cyril J. Michel; Arnold J. Ammann; Eric D. Chapman; Philip T. Sandstrom; Heidi E. Fish; Michael J. Thomas; Gabriel P. Singer; Steven T. Lindley; A. Peter Klimley; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Diel movements of out-migrating Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) smolts in the Sacramento/San Joaquin watershed - Eric D. Chapman; Alex R. Hearn; Cyril J. Michel; Arnold J. Ammann; Steven T. Lindley; Michael J. Thomas; Philip T. Sandstrom; Gabriel P. Singer; Matthew L. Peterson; R. Bruce MacFarlane; A. Peter Klimley (Environmental Biology of Fishes, 2013)

Revisiting the evolution of ecological specialization, with emphasis on insect–plant interactions - M. L. Forister; L. A. Dyer; M. S. Singer; J. O. Stireman; J. T. Lill (Ecology, 2012)
Ecological specialization is a fundamental and well‐studied concept, yet its great reach and complexity limit current understanding in important ways. More than 20 years after the publication of D. J. Futuyma and G. Moreno's oft‐cited, major review of the topic, we synthesize new developments in the evolution of ecological specialization. Using insect–plant interactions as a model, we focus on important developments in four critical areas: genetic architecture, behavior, interaction complexity, and macroevolution. We find that theory based on simple genetic trade‐offs in host use is being replaced by more subtle and complex pictures of genetic architecture, and multitrophic interactions have risen as a necessary framework for understanding specialization. A wealth of phylogenetic data has made possible a more detailed consideration of the macroevolutionary dimension of specialization, revealing (among other things) bidirectionality in transitions between generalist and specialist lineages. Technological advances, including genomic sequencing and analytical techniques at the community level, raise the possibility that the next decade will see research on specialization spanning multiple levels of biological organization in non‐model organisms, from genes to populations to networks of interactions in natural communities. Finally, we offer a set of research questions that we find to be particularly pressing and fruitful for future research on ecological specialization.

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Effects of nadir CD4 count and duration of human immunodeficiency virus infection on brain volumes in the highly active antiretroviral therapy era - Ronald A Cohen; Jaroslaw Harezlak; Giovanni Schifitto; George Hana; Uraina Clark; Assawin Gongvatana; Robert Paul; Michael Taylor; Paul Thompson; Jeffery Alger; Mark Brown; Jianhui Zhong; et al. (Journal of NeuroVirology, 2010)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Probability distributions for carbon emissions and atmospheric response - Clifford E. Singer; T. S. Gopi Rethinaraj; Samuel Addy; David Durham; Murat Isik; Madhu Khanna; Brandon Kuehl; Jianding Luo; Wilma Quimio; Kothavari Rajendran; Donna Ramirez; Ji Qiang; et al. (Climatic Change, 2008)

Nest demographics and foraging behavior of Apterostigma collare Emery (Hymenoptera, Formicidae) provide evidence of colony independence - T. L. Pitts-Singer; K. E. Espelie (Insectes Sociaux, 2007)

Clues about the ancestral roles of plant MADS-box genes from a functional analysis of moss homologues - S. D. Singer; N. T. Krogan; N. W. Ashton (Plant Cell Reports, 2007)

Cover crop effects on the fate of N following soil application of swine manure - T. B. Parkin; T. C. Kaspar; J. W. Singer (Plant and Soil, 2006)

See globally, spike locally: oscillations in a retinal model encode large visual features - Greg J. Stephens; Sergio Neuenschwander; John S. George; Wolf Singer; Garrett T. Kenyon (Biological Cybernetics, 2006)

Acquired and Partially De Novo Synthesized Pyrrolizidine Alkaloids in Two Polyphagous Arctiids and the Alkaloid Profiles of Their Larval Food-Plants - T. Hartmann; C. Theuring; T. Beuerle; L. Ernst; M. S. Singer; E. A. Bernays (Journal of Chemical Ecology, 2004)

Experience influences gustatory responsiveness to pyrrolizidine alkaloids in the polyphagous caterpillar, Estigmene acrea - R. F. Chapman; E. A. Bernays; M. S. Singer; T. Hartmann (Journal of Comparative Physiology A, 2003)

Topotecan in the Treatment of Acquired Immunodeficiency Syndrome-Related Progressive Multifocal Leukoencephalopathy - W Royal III; B Dupont; D McGuire; L Chang; K Goodkin; T Ernst; MJ Post; D Fish; G Pailloux; H Poncelet; M Concha; L Apuzzo; et al. (Journal of NeuroVirology, 2003)

Influence of Guidelines and Passageways on Tunneling Behavior of Reticulitermes flavipes (Kollar) and R. virginicus (Banks) (Isoptera: Rhinotermitidae) - Theresa L. Pitts-Singer; Brian T. Forschler (Journal of Insect Behavior, 2000)

The chemical cell biology of zinc: structure and intracellular fluorescence of a zinc-quinolinesulfonamide complex - M. Sarwar Nasir; Christoph J. Fahrni; David A. Suhy; Kevin J. Kolodsick; Christopher P. Singer; T. V. O'Halloran (JBIC Journal of Biological Inorganic Chemistry, 1999)

Frequency of partial and missing rings in Acer saccharum in relation to canopy position and growth rate - Craig G. Lorimer; Sally E. Dahir; Matthew T. Singer (Plant Ecology, 1999)

Population subdivision among desert bighorn sheep ( Ovis canadensis ) ewes revealed by mitochondrial DNA analysis - W. M. Boyce; R. R. Ramey; T. C. Rodwell; E. S. Rubin; R. S. Singer (Molecular Ecology, 1999)
We used behavioural observations and mitochondrial DNA (mtDNA) sequence analysis to examine demographic and genetic structure within and among home‐range groups of desert bighorn sheep ( Ovis canadensis ) ewes in the Peninsular Ranges of southern California, USA. We identified substantial genetic variation in the first 515 bp of the mtDNA control region and determined that seven haplotypes were distributed in a nonrandom fashion among these ewe subpopulations. Although a significant ( P

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Characterization of two class I genes from the H2-M region: evidence for a new subfamily - S. R. Arepalli; Elsy P. Jones; T. Kevin Howcroft; Irene Carlo; C.-R. Wang; K. Fischer Lindahl; Dinah S. Singer; Stuart Rudikoff (Immunogenetics, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

HIV-gp120 induced cell death in hematopoietic progenitor CD34+ cells - N. K. Banda; J. A. Tomczak; E. J. Shpall; J. Sipple; R. K. Akkina; K. S. Steimer; L. Hami; T. J. Curiel; G. Singer Harrison (Apoptosis, 1997)